THE ROLE OF FAMILY BUSINESSES IN THE ECONOMY OF THE COUNTRY: THE EXAMPLE OF BUKHARA REGION - Jafarova Khilola Khalimovna (Лучшие интеллектуальные исследования, 2024)
Annotation. Bukhara in the region family enterprises big share occupies _ The importance of family enterprises in the economy of Bukhara region is increasing year by year. In the province, family enterprises are mainly in the fields of agriculture, forestry and fisheries, industry, construction, trade, transportation and storage, accommodation and food services, information and communication, as well as health and social services. are conducting their activities. According to the Law of the Republic of Uzbekistan "On Family Entrepreneurship", family entrepreneurship is an entrepreneurial activity carried out by family members with the purpose of obtaining income (profit) at the risk and under their own property responsibility. As defined in this law, family business can be carried out with or without the establishment of a legal entity at the discretion of the family members.